Vegetative propagation of rootstock selections potentially tolerant to Peach Tree Short Life - Mayer, Newton Alex; Ueno, Bernardo; Neves, Tainá Rodrigues das (Revista de Ciências Agroveterinárias, 2018)
Peach Tree Short Life (PTSL) is a syndrome that involves several biotic and abiotic agents. Seeking to reduce losses, the main research line has been the search for tolerant rootstocks. Among desirable characteristics in an appropriate rootstock, the ease of vegetative propagation is fundamental to preserve genetic identity and facilitate the diffusion of technologies. The objective of this research was to evaluate the technical feasibility of vegetative propagation by herbaceous stem cuttings of 18 clonal rootstock selections [Prunus persica (L.) Batsch.], potentially tolerant to PTSL, under intermittent mist system. As reference rootstock cultivars, 'Capdeboscq', 'Okinawa' (P.persica) and 'Sharpe' ['Chickasaw' (Prunus angustifolia Marsh.) x Prunus spp.] were used. From the evaluations after 65 days of cutting set, it was possible to conclude that the propagation of rootstock selections by herbaceous cuttings is technically feasible, with rooting percentages varying from 21.67% to 91.67%; thus, none of these genotypes should be discarded from the selection process. The quality of the adventitious roots formed was satisfactory in most of the studied genotypes, with high cuttings percentage suitable for transplanting, satisfactory root number and root length. However, the selection WFM-ESM-07-04 and cultivars Capdeboscq and Sharpe stood out positively in this aspect. Among the three reference rootstocks, 'Okinawa' and 'Capdeboscq' showed very similar propagative capacity (yield) for herbaceous cuttings, but both are better than 'Sharpe'.